ANALISIS FAKTOR USIA DAN PEKERJAAN TERHADAP TERJADINYA PENYAKIT HIPERTENSI - Wahyuni, Wahyuni; Ardika, Noviana Ayu; Noorratri, Erika Dewi (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2024)
Background: As age increases, the proportion of elderly people who experience health complaints increases and the risk of developing hypertension becomes greater, namely around 40% who suffer from hypertension is quite high, especially among the elderly. According to the results of a study, there is an influence of age variables on the incidence of hypertension, while according to other studies, age and work related to socio-economics are factors that have a significant influence on the incidence of hypertension. The purpose of this study was to analyze age and work factors on hypertension in the elderly in the Kratonan Health Center work area. This research method uses a descriptive research method with 164 respondents using quota sampling techniques with chi square data analysis. Results: Most respondents are of productive age, namely 83.5%, the majority of respondents work in the private sector, namely 41.5%, the majority of respondents do not suffer from hypertension, namely 80%, based on bivariate analysis, it was found that there is a relationship between work and hypertension with a P value of 0.000 and there is a relationship between age and hypertension with a P value of 0.000. Conclusion: there is a relationship between work and age and hypertension.